Prevalência de fissuras orais de 1975 a 1994 Prevalence of oral clefts from 1975 to 1994, Brazil - Leonor de Castro Monteiro Loffredo; José Alberto de Souza Freitas; Ana A Gomes Grigolli (Universidade de São Paulo, 2001)
OBJETIVO: Estimar a prevalência de fissuras orais no Brasil, segundo etiologia e região geográfica. MÉTODOS: Foram levantados os registros de casos de fissura oral entre recém-nascidos no período de 1975 a 1994. As fontes de dados foram o Hospital de Reabilitação de Anomalias Craniofaciais da Universidade de São Paulo, o Ministério da Saúde -- Departamento de Informática do Sistema Único de Saúde (Datasus) e a Fundação Instituto Brasileiro de Geografia e Estatística. RESULTADOS/CONCLUSÕES: Foram encontrados 16.853 casos novos de fissura oral, estimando-se a prevalência de 0,19 por mil nascidos vivos, com tendência ascendente para os qüinqüênios do período. As regiões Centro-Oeste, Sudeste e Sul apresentaram as maiores taxas. A fissura labial ou lábio-palatina foi mais freqüente (74%) do que a fissura palatina isolada (26%). OBJECTIVE: To estimate the prevalence of oral clefts in Brazil categorized by etiology and geographical region. METHODS: Case reports of oral cleft in newborns in the period 1975--1994 were included in the study. Data was collected using the morbidity certificates of the Hospital de Reabilitação de Anomalias Craniofaciais (Craniofacial Abnormalities Rehabilitation Hospital), Ministry of Health data (Datasus), and Fundação Instituto Brasileiro de Geografia e Estatística (Brazilian Census Bureau). RESULTS/CONCLUSIONS: There were 16,853 new cases of oral clefts, with a total prevalence of 0.19 per 1,000 births, and there was an increased prevalence every five years. The highest prevalence were observed in the Midwest, southeast, and south regions. As for the studied categories, cleft lip (or the cleft of lip and palate) was seen in 74% of the cases and isolated cleft palate was seen in 26% of them.